Intensitas ektoparasit pada Kepiting Bakau (Scylla serrata) di tambak Desa Sagintung Kecamatan Seruyan Hilir - Sri Herlina (Fakultas Peternakan Universitas Kristen Palangka Raya, 2017)
This study aims to determine the types of ectoparasites that attack mangrove crabs and calculate the level of intensity of ectoparasites attacks on mangrove crabs (Scylla serrata) that rearing at the Sagintung village pond. This research was conducted in July - August 2017. Samples of mangrove crabs taken as many as 100 tail. The results of the observation were 4 species of Protozoa namely Zoothamnium sp, Epistylis sp, Vortecella sp and 1 species of Arthropoda namely Octolasmis sp. Intensity of ectoparasite attack on carapace 8.0%, swimming legs 2%, legs 2% and gills 87%. The total intensity attack of Zoothamnium sp., Epistylis sp., Vorticella sp., and Octolasmis sp. were 40%. Key words : Ectoparasites, Scylla serrata, Intensity, pond.